International marketing : strategy and theory - Onkvisit, Sak; Merz, Michael A., 1976-; Shaw, John J. (Routledge, 2025)
"This comprehensive text provides students with a solid foundation in International Marketing theory, research, and practice. Fully updated throughout, the book covers all the latest trends and topics, including e-commerce, digitalization, corporate sustainability, business ethics, corporate social responsibility, cryptocurrency, and the broader political and economic context. New international case studies and mini-cases from the US, Europe, China and Japan are incorporated, alongside enhanced pedagogy to structure learning such as chapter objectives, summaries and discussion questions. Placing a unique emphasis on the importance of academic research, all academic references and marketing theories have also been updated. Demonstrating the complexities of marketing on a global scale, this well-regarded text should be core reading for advanced undergraduate and postgraduate students of International and Global Marketing, Marketing Management and Strategic Marketing. Online resources include chapter-by-chapter PowerPoint slides, a test bank, cases and discussion questions, and videos to accompany specific topics"-- Provided by publisher.